CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst and application thereof in preparation of aryl formonitrile by catalyzing methyl aromatic hydrocarbon
The CsPb2Br5/Na2Ti3O7 nanotube composite catalyst catalyzes the ammoxidation of methylaromatic hydrocarbons under low temperature and low pressure conditions, solving the environmental protection and safety issues of traditional high temperature and high pressure catalytic methods, and achieving catalytic effects with high selectivity and high conversion rate.
Patent Information
- Application Number
- CN202411458859.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, when catalyzing methylaromatic hydrocarbons to prepare aromatic oxidine, high temperature and high pressure conditions are required, environmental protection and safety problems are encountered, and the catalyst costs are high and by-products are difficult to handle.
The CsPb2Br5/Na2Ti3O7 nanotube composite catalyst is used to form a catalyst with a coupling effect by combining CsPb2Br5 and Na2Ti3O7 nanotubes to achieve ammoxidation of methyl aromatic hydrocarbons under low temperature and low pressure conditions.
The high -selectability and high conversion rate of methyl -based aromatics of hydrocarbon ammonia oxidation under low temperature and low pressure conditions have achieved good stability and repetitive utilization, reducing production costs and environmental protection pressure.
Smart Images

Figure CN119346141A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst and a preparation method thereof and application thereof in catalyzing methyl aromatic hydrocarbons to prepare aromatic nitrile, belonging to the technical field of photocatalytic preparation of chemicals. Background Art
[0002] CsPb2Br5 is a new type of inorganic perovskite material, belonging to the cesium lead halide perovskite series, with a unique structure and excellent photoelectric properties. Its chemical formula indicates that each unit cell contains two lead (Pb 2+ ) ions and five bromine (Br - ) ion, combined with a cesium (Cs + ) ions. Its crystal structure has the characteristics of a perovskite, but it is different from the traditional ABX3-type perovskite. In CsPb2Br5, lead ions and bromide ions are arranged in a different way to form a perovskite framework with a layered structure, while cesium ions are located in the gaps of the structure.
[0003] The photoelectric properties of CsPb2Br5 materials are very good, with excellent photoelectric conversion performance, which enables the material to efficiently convert light energy into chemical energy, thereby significantly improving the efficiency of catalytic reactions, and therefore has unique advantages in catalytic applications. In addition, lead-based perovskites have a wide spectral response range and can maintain efficient catalysis under illumination conditions from ultraviolet to visible light. Their high catalytic activity ensures excellent performance in various organic reactions and can improve reaction rates and selectivity. Moreover, lead-based perovskites exhibit good structural stability during the catalytic process, can maintain their catalytic performance during long-term use, and reduce catalyst degradation. Its synthesis method is simple, and the catalytic performance can be optimized by adjusting the composition and structure of the material to achieve precise control of the reaction process. These characteristics make lead-based perovskites have a wide range of application potential in the field of organic catalysis, especially in environmental remediation and green chemical synthesis. It has important application value. Compared with other lead-containing perovskite materials, CsPb2Br5 may have better environmental stability and lower risk of lead leakage. Overall, CsPb2Br5 has become an important research object in the field of materials science and optoelectronics due to its unique structure and excellent photoelectric properties.
[0004] Na2Ti3O7 nanotubes have been widely studied due to their uniform tubular microstructure, high specific surface area, efficient photoelectric conversion performance and good solution stability, and are currently an excellent choice for industrial production and basic research. Their high specific surface area allows the surface of the unit mass of Na2Ti3O7 nanotube catalyst to adsorb more solution components, while their smaller volume also reduces the distance and time required for photogenerated electrons and holes to diffuse to the surface, reducing the recombination rate of photogenerated electrons and holes and increasing the photon quantum yield.
[0005] The cyano group of aromatic nitriles has high reactivity. Through hydrolysis, hydrogenation, addition, polymerization and other reactions, a series of fine chemicals such as amides, acids, aromatic amines, heterocyclic compounds can be obtained. They are important raw materials for the manufacture of pesticides, medicines, dyes, fragrances, optoelectronic materials, resins, etc. Traditional benzonitrile synthesis methods, such as Sandmeyer reaction and benzaldehyde cyanation reaction, are superior in product purity and reaction selectivity, but the toxic chemicals and waste treatment issues involved make these methods challenging in terms of environmental protection and safety. Modern synthesis methods such as gas-phase ammonia oxidation and direct amination provide more environmentally friendly and economical options, but usually require more stringent operating conditions, such as high temperature and pressure, and there are also problems such as high catalyst cost and difficult to handle by-products, which still need to be further optimized. The continuous improvement and optimization of these new methods are expected to further enhance their wide application and economic efficiency. Summary of the invention
[0006] The purpose of the present invention is to provide a novel composite catalyst which can be used for green synthesis of aromatic nitrile under low temperature and low pressure conditions.
[0007] The technical solution adopted by the present invention is:
[0008] A CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst is characterized in that it is composited with CsPb2Br5 and Na2Ti3O7 nanotubes, wherein the mass ratio of CsPb2Br5 is 5-25%.
[0009] The present invention also discloses a method for preparing the aforementioned CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst, the steps of which include:
[0010] (1) preparing Na2Ti3O7 nanotubes, or directly using commercially available Na2Ti3O7 nanotubes;
[0011] (2) adding CsBr and PbBr2 into DMF at a molar ratio of 1:2 to obtain a DMF solution containing CsBr and PbBr2; or directly using a DMF solution of CsPb2Br5; or directly using a DMF solution of CsPb2Br5;
[0012] (3) Adding Na2Ti3O7 nanotubes into DMF solution, grinding them evenly and then drying to remove DMF, thereby obtaining CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst.
[0013] Preferably, step (1) is specifically as follows: adding anatase TiO2 to a NaOH solution and stirring for a period of time, transferring the mixed suspension to an autoclave, sealing and heating to generate Na2Ti3O7 nanotubes, washing the obtained suspension, filtering it with suction, drying it in an oven, then grinding the obtained material and placing it in a muffle furnace, heating and roasting it to obtain Na2Ti3O7 nanotubes. The preparation method of Na2Ti3O7 nanotubes is a prior art, and other disclosed technologies can also be used to prepare Na2Ti3O7 nanotubes, wherein the TiO2 is anatase TiO2. Na2Ti3O7 nanotubes prepared from other crystal forms of TiO2 are used to prepare CsPb2Br5 / Na2Ti3O7 nanotube composite catalysts, and the catalytic effect is significantly lower than that of anatase TiO2.
[0014] Preferably, the concentration of the NaOH solution is 10 M, the stirring is performed for 1.5 h, the heating treatment temperature is 150° C., and the treatment time is 72 h.
[0015] The aforementioned CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst is used in catalyzing the preparation of aromatic nitrile from methyl aromatic hydrocarbons.
[0016] Preferably, a CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst is added to a methyl aromatic hydrocarbon solution, and a light source is provided to irradiate the solution, and aromatic nitrile is generated in a mixed atmosphere of O2 and NH3. The reaction formula is as follows (1):
[0017]
[0018] Preferably, the reaction temperature is between 100 and 140° C., the reaction pressure is between 1 and 5 bar, and O2 accounts for 20 to 80% of the mixed atmosphere of O2 and NH3.
[0019] Preferably, the light source used is a monochromatic light source with a wavelength of 365-450 nm, or a composite light source containing the aforementioned monochromatic light.
[0020] Preferably, the methyl aromatic hydrocarbon is toluene, p-chlorotoluene, p-bromotoluene or 4-methyltrifluorotoluene.
[0021] The present invention adopts a simple method to synthesize a very effective oxide composite catalyst CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst, and successfully applies it to the selective photocatalytic ammoxidation of methyl aromatics. By using this composite catalyst for the selective photocatalytic ammoxidation of methyl aromatics, a selectivity of 81% can be obtained, and the yield of aromatic nitrile is about 0.93g·g cat -1 ·day -1 .
[0022] The beneficial effects of the present invention are as follows:
[0023] (1) The present invention provides a method for preparing a CsPb2Br5 / Na2Ti3O7 nanotube composite material, wherein Na2Ti3O7 nanotubes are used as the main component and CsPb2Br5 is distributed on the surface of the Na2Ti3O7 nanotubes. The entire preparation process is simple, the conditions are controllable, and the cost is low. The synthesized material has a small particle size and a large specific surface area (243 m 2 / g) characteristics.
[0024] (2) The CsPb2Br5 / Na2Ti3O7 nanotube composite material provided by the present invention has a coupling effect, which can realize the liquid-phase methyl aromatic ammoxidation under visible light, especially the toluene ammoxidation under low temperature and low pressure (minimum reaction temperature 100°C, minimum reaction pressure 1 bar); and the catalyst can maintain a high benzonitrile selectivity (up to 81%) during long-term reaction under the condition of sufficient gas, showing good stability and reusability, and has the potential for practical application.
[0025] (3) CsPb2Br5, which can efficiently activate toluene, was used as a photocatalyst and loaded on Na2Ti3O7 nanotubes to form a composite catalyst, which achieved high selectivity and high conversion rate of photocatalytic methyl aromatic ammoxidation at low temperature and low pressure, providing a new idea for further reducing the temperature of the methyl aromatic ammoxidation reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 , Transmission electron microscope (TEM) photograph of the catalyst sample prepared in Example 1.
[0027] Figure 2 , X-ray diffraction data (XRD) of the catalyst sample prepared in Example 1.
[0028] Figure 3 , the relationship between the product yield and selectivity in Example 2 and the change in CsPb2Br5 loading.
[0029] Figure 4 , GC-MS of the product in Example 2. DETAILED DESCRIPTION
[0030] Example 1: Preparation of photocatalyst
[0031] Taking CsPb2Br5 / Na2Ti3O7 nanotubes with a CsPb2Br5 loading of 10wt% as an example, the preparation method is as follows:
[0032] Weigh 2g TiO2 (anatase type) into a plastic bottle, add 40mL of 10M NaOH and stir for 1.5h, transfer the mixed suspension into a 100mL polytetrafluoroethylene-lined autoclave, seal and heat treat in an oven at 150℃ for 72h to produce nanotubes, wash the obtained suspension with water until the pH value of the washing liquid reaches about 7, filter the obtained material and dry it in a blast oven at 70℃, then grind the obtained material and put it into a muffle furnace, heat it to 300℃ at a heating rate of 2℃ / min, and roast it for 3 hours. After the roasting is completed, wait for natural cooling, take it out of the furnace, and obtain about 1.8g Na2Ti3O7 nanotube product. 180 mg of the calcined Na2Ti3O7 nanotube sample was weighed and mixed with 200 μL of DMF solution, wherein the DMF solution contained CsBr and PbBr2 precursors, and the molar ratio of CsBr and PbBr2 was controlled to be 1:2. For example, a 10 wt% CsPb2Br5 / Na2Ti3O7 nanotube sample required the addition of 4.49 mg CsBr and 15.5 mg PbBr3 in DMF. After grinding in an agate mortar for 20 min, the mixture was dried in an oven at 120 °C for 12 h. The prepared catalyst was characterized as shown in FIG. Figure 1-2 shown. Figure 1 Transmission electron microscope image of the catalyst sample. Figure 2 The XRD data of the catalyst sample. According to statistics, the average particle size of the prepared CsPb2Br5 nanoparticles is 1.5nm, the average diameter of the Na2Ti3O7 nanotubes is 10nm, and the average length is 102nm.
[0033] By changing the dosage ratio of Na2Ti3O7 nanotubes and DMF solution, CsPb2Br5 / Na2Ti3O7 nanotube composite catalysts with other loading amounts can be obtained.
[0034] Example 2: Preparation of benzonitrile
[0035] Weigh 70 mg of CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst with different loadings, wash and dry it with acetone and formic acid mixed solution (acetone: formic acid = 1:1), put it in a reactor, add 5 mL of toluene, replace the reaction system with 60% O2+40% NH3, turn on the 410nm LED light source, and irradiate the reaction for 10 hours. After the reaction is completed, turn off the light source, centrifuge the reaction mixture, pour out the supernatant, and filter the catalyst solid with a filter membrane to obtain the target product. The obtained product was tested for performance by GC, GC-MS, etc. At a loading rate of 10wt%, about 1g / (g·d) of benzonitrile was obtained, and the selectivity was about 81%. Using the same mass of CsPb2Br5 or Na2Ti3O7 nanotubes as a control, the relationship between product yield and selectivity with loading is shown in Figure 3 , the GC-MS images of the products are shown in Figure 4 The selectivity of the above reaction formula and its corresponding product is shown in the following formula (2):
[0036]
[0037] Comparative Example 1: Using rutile TiO2 instead of anatase TiO2, a CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst with a loading of 10% was prepared in the same manner as in Example 1, and was used to catalyze the preparation of benzonitrile. The reaction conditions were the same as in Example 2, and a benzonitrile yield of 18.4 μmol was obtained, and the benzonitrile selectivity was 55.2%.
[0038] Embodiment 3:
[0039] Benzonitrile was prepared under the same conditions as in Example 2, with a loading of 10% of the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst, and an LED light source with a wavelength of 450 nm was used for 10 h of irradiation, and the yield of benzonitrile in the product was 155.6 μmol, and the selectivity of benzonitrile in the product was 82%. When an LED light source with a wavelength of 365 nm was used for 10 h of irradiation, the yield of benzonitrile was 464 μmol, and the selectivity of benzonitrile was 61%.
[0040] Embodiment 4:
[0041] Benzonitrile was prepared under conditions substantially the same as those in Example 2. The loading amount of the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst was 10%. When the reaction temperature was adjusted to 100°C, the benzonitrile yield was 50.8 μmol, and the benzonitrile selectivity was 83%. When the reaction temperature was adjusted to 140°C, the benzonitrile yield was 451 μmol, and the benzonitrile selectivity was 64%.
[0042] Example 5
[0043] Benzonitrile was prepared under conditions substantially the same as those in Example 2, with a loading of 10% for the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst. When the pressure was adjusted to 1 bar, the benzonitrile yield was 117.3 μmol, and the benzonitrile selectivity was 47%; when the pressure was adjusted to 5 bar, the benzonitrile yield was 121.5 μmol, and the benzonitrile selectivity was 73%.
[0044] Example 6
[0045] Benzonitrile was prepared under conditions substantially the same as those in Example 2, with a loading of 10% for the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst. When the oxygen content in the reaction gas was adjusted to 20%, the benzonitrile yield was 143.7 μmol, and the benzonitrile selectivity was 76%. When the oxygen content was adjusted to 80%, the benzonitrile yield was 322.8 μmol, and the benzonitrile selectivity was 65%.
[0046] Example 7: Using conditions substantially the same as those in Example 2, p-chlorotoluene was used as a substrate to prepare p-chlorobenzonitrile. The amount of substrate used was 5 ml, the reaction time was 6 h, the yield was 114 μmol, and the selectivity was ≧90%.
[0047] Example 8: Using conditions substantially the same as those in Example 2, p-bromotoluene was used as a substrate to prepare p-bromobenzonitrile. The amount of substrate used was 5 ml, the reaction time was 6 h, the yield was 106 μmol, and the selectivity was ≧90%.
[0048] Example 9: Using conditions substantially the same as those in Example 2, 4-methyltrifluorotoluene was used as a substrate to prepare p-trifluoromethylbenzonitrile. The amount of substrate used was 5 ml, the reaction time was 6 h, the yield was 52 μmol, and the selectivity was ≧90%.
[0049] In summary, the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst provided by the present invention has a coupling effect and can realize liquid-phase toluene ammoxidation under visible light; and the catalyst has high selectivity and conversion rate under the condition of sufficient gas, has the potential for practical application, and solves the drawbacks of high temperature and high pressure in current production. Due to the milder reaction conditions, the new method of the present invention can prepare a series of nitrile organic compounds, which can be applied in chemical production, chemical reaction mechanism and other aspects.
Claims
1. A CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst, characterized in that By Cs The composite is composed of Pb2Br5 and Na2Ti3O7 nanotubes, wherein the mass ratio of CsPb2Br5 is 5-25%.
2. The method for preparing the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst according to claim 1, characterized in that: The steps include: (1) adding CsBr and PbBr2 into DMF at a molar ratio of 1:2 to obtain a DMF solution containing CsBr and PbBr2; or directly using a DMF solution of CsPb2Br5; (2) Na2Ti3O7 nanotubes are added to DMF solution, ground evenly, and then dried to remove DMF to obtain CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst.
3. The preparation method according to claim 2, characterized in that: The preparation method of Na2Ti3O7 nanotubes is as follows: adding anatase TiO2 to a NaOH solution and stirring for a period of time, transferring the mixed suspension to an autoclave, sealing and heating to generate Na2Ti3O7 nanotubes, washing the obtained suspension and filtering it, drying it in an oven, then grinding the obtained material and placing it in a muffle furnace, heating and calcining it to obtain Na2Ti3O7 nanotubes.
4. The preparation method according to claim 3, characterized in that: The concentration of the NaOH solution was 10 M, the stirring was performed for 1.5 h, the heating temperature was 150° C., and the treatment time was 72 h.
5. Use of the CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst according to claim 1 in catalyzing the preparation of aromatic nitrile from methyl aromatic hydrocarbons.
6. The use according to claim 5, characterized in that: A CsPb2Br5 / Na2Ti3O7 nanotube composite catalyst is added to a methyl aromatic solution and irradiated with a light source to generate aromatic nitrile in a mixed atmosphere of O2 and NH3.
7. The use according to claim 6, characterized in that: The reaction temperature is between 100 and 140° C., the reaction pressure is between 1 and 5 bar, and O2 accounts for 20 to 80% of the mixed atmosphere of O2 and NH3.
8. The use according to claim 6, characterized in that: The light source used is a monochromatic light source with a wavelength of 365 to 450 nm, or a composite light source containing the aforementioned monochromatic light.
9. The use according to any one of claims 5 to 8, characterized in that: The methyl aromatic hydrocarbon is toluene, p-chlorotoluene, p-bromotoluene or 4-methyltrifluorotoluene.